Homophobic violence: analysis of intolerance crimes against the LGBT community in Belém-PA - Formento, Jacyara dos Anjos Sarges (2020)
The article aims to analyze the records of homophobic crimes, which occurred in the years 2017 and 2018 from the police reports registered with the Police Station for Combating Discriminatory and Homophobic Crimes, located in Belém-PA. For data analysis, documentary research was carried out, with the survey of police reports registered with the specialized police station, included in the SISP 2 system, of the Civil Police of the State of Pará, using the Exploratory Analysis technique. It was observed that the majority of the victims are male, injuries were the most common type of crime, which occurred in the private residence, on Sundays and Wednesdays, in the afternoon shift, most of the records were converted into police procedures. It is concluded that homophobic violence is a public health and safety problem, and although there has been an advance in national legislation, there is still a long way to go to achieve the expected degree of protection and punishment for those involved.